1997
DOI: 10.1046/j.1524-475x.1997.50407.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal lipid metabolism of cultured skin substitutes during healing of full‐thickness wounds in athymic mice

Abstract: Cultured epidermal keratinocytes provide an abundant supply of biologic material for wound treatment. Because restoration of barrier function is a definitive criterion for efficacy of wound closure and depends on the lipids present in the epidermis, we analyzed lipid composition of the epidermis in cultured skin substitutes in vitro and after grafting to athymic mice. The cultured skin substitutes were prepared from human keratinocytes and fibroblasts attached to collagen-glycosaminoglycan substrates. After 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 12 publications
0
12
1
Order By: Relevance
“…3A). In contrast to our results, previous reports found that in cultured skin substitutes grown in vitro the levels of cholesterol and free fatty acids were increased during the healing process with grafting [10,26]. An increase in the levels of lipids in HDFn, in particular sphingolipids such as ceramides and glucosylceramides, has been noted to occur in the wound healing process [27,28].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…3A). In contrast to our results, previous reports found that in cultured skin substitutes grown in vitro the levels of cholesterol and free fatty acids were increased during the healing process with grafting [10,26]. An increase in the levels of lipids in HDFn, in particular sphingolipids such as ceramides and glucosylceramides, has been noted to occur in the wound healing process [27,28].…”
Section: Discussioncontrasting
confidence: 99%
“…Recent evidence indicates that increased lipid biosynthesis may also enhance wound healing closure and restoration of the barrier function of the skin during the wound healing process. The skin barrier is formed from the lipid-enriched membrane of the stratum corneum, which is the outer most layer of the epidermis, and is organized with a repetitive lamellar structure of sphingolipids, cholesterol, and fatty acids [3,10]. Reduced lipid synthesis delays wound healing [11] and enhanced wound closure with an increased level of skin barrier lipids has been reported during the wound healing process of skin [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In the stratum corneum of HSEs, the chain length of FFAs is shorter when compared to native human skin, but improvement of the lipid profile has been achieved by the supplementation of fatty acids in the medium . More recently, two different HSE and one HEE model and their ceramide profiles were examined .…”
Section: D Skin Models To Study the Physical Skin Barrier: From Stramentioning
confidence: 99%
“…FFAs, naturally present in the SC, predominantly have saturated and straight chains of 22 (docosanoic acid), 24 (lignocerin acid) and 26 (hexacosanoic acid) carbon atoms [3,4]. Oleic and linoleic acids are the only unsaturated fatty acids detected in SC [5]. Freeze-fracture [6,7] and ruthenium tetroxide post-fixation [8] electron microscopy studies revealed that lipids are arranged into bilayers [9,10].…”
Section: Introductionmentioning
confidence: 99%